[Student in Yosemite dorm room] (1977)
One student sits with head propped up in her hands, smiling towards the camera, behind a desk covered in houseplants and a decorative lamp. A guitar sits against the desk, and a chair and other decorations are sitting in the background. Many posters and a calendar are hanging on the cabinets facing the rear of the room. A small cutout of Woodstock from Charles Schulz's 'Peanuts' comic strip sits on the desk. A woven basket (possibly a lamp or plant holder?) hangs above the student's head.